The Influence Of Maxim Food Courier Service Quality On Customer Satisfaction Of Bri Employees Bengkulu Branch Office - Dwiki Kurniawan; Iswidana Utama Putra; Lydia Gustina Putri (Universitas Dehasen Bengkulu, 2026)
In the current era of digitalization, interactions between companies and consumers have undergone significant changes, particularly in service sectors such as MaximFood, where service quality greatly influences customer satisfaction. In this context, the MaximFood delivery service company seeks to understand how service quality affects customer satisfaction.This study aims to determine the effect of MaximFood courier service quality on customer satisfaction among employees of the BRI Bengkulu Branch Office. This research employs a quantitative approach, in which data collection is represented numerically to obtain information and draw conclusions.The study population consists of all employees of the BRI Bengkulu Branch Office. Sampling was carried out using a saturated sampling method, involving all 60 respondents in the population. According to Kuncoro, a correlational study requires at least 30 samples to test whether a relationship exists between variables.The results show that the service quality of the MaximFood courier has a significant effect on customer satisfaction among employees of the BRI Bengkulu Branch Office. Based on the t-test, the obtained significance value is 0.000, which is smaller than the threshold value of 0.05. This indicates that the hypothesis stating that service quality significantly affects customer satisfaction is accepted.Furthermore, the coefficient of determination (R²) value is 0.619 or 73.4%, meaning that 73.4% of customer satisfaction is influenced by the quality of MaximFood’s courier service, while the remaining 26.6% is affected by other variables outside the regression model.